Internet television an initial market assessment - Tusara, Laarni M. (University of the Philippines Diliman, 2007)
Traditional and new television content are more commonly seen over the Internet due to the advances in technology. Increase in speed of Internet connection and total Internet users and decrease in connection cost allows the convergence of Internet and television, two media which were once seen separately to deliver distinct purposes. The move from broadcast television to broadband television only entails wider content selection for Internet users. Local free television as well as cable and satellite companies can only offer as much channels, but come the blurring of Internet and television, it is but unimaginable to see the vastness of possible content features available. This study looks at the potential of a new technology where television content is delivered through broadband network instead of the usual broadcast and cable formats. Internet Television is already present in more technologically advanced areas in Europe and the United States. It has been criticized for a number of hurdles like the lack of set top boxes to convert analog channels to digital format, low bandwidth in the household, and the anticipated poor quality of the streaming video. Internet TV however offers interactivity and convergence. The broadcast industry recognized that more television shows are also viewed through new media devices apart from the tradition television sets. Mobile phones, iPod and especially the Internet, are venues where one can provide content for television viewers and Internet users alike. The immergence of these new media would offer opportunities for broadcast companies apart from the revenues generated from airtime sales. Since we are dealing with a new technology, it is important to identify key product and market information valued by the potential subscribers of Internet Television. This study intends to determine the features that are considered strengths and weaknesses of Internet Television, substantiate how much the market is willing to pay for the subscription of Internet Television and identify the market segment most likely to use Internet Television. The Theory of Reasoned Action developed by Ajzan and Fishbien in 1967 was used as the framework for this research. Theory of Reasoned Action implies that prior attitude toward the behavior and the present subjective norms influence an individual's intention. A person will normally act in accordance with his intentions. Thus, the easiest way to predict a behavior, for example, whether a consumer will purchase a product, like Internet TV is to simply ask if they are interested to subscribe to Internet TV. The attitude and subjective norms are operationalized through factors like market needs, wants, considerations, influences, etc. This research used a concept test questionnaire administered through face to face and email to 115 respondents purposively chosen. Concept testing is a special method in market research that assesses new product idea. This is very useful since the market's preference and purchase intentions are exploded before the actual launch of the product. For the purpose of this study, the Internet Television concept, made by the researcher reads : Internet TV give you choice and convenience. You can count on having a wide choice of archived features like movies, television shows and series, music videos, concerts, interviews, documentaries, etc., ready to be retrieved anytime, whenever you want. With INTERNET TV, you will experience the convenience of watching whatever you want, in the comfort of your own home. No need to wait for regular programming. No need to rent or purchase CDs. On top of this is a variety of channels (i.e., local. International, cartoon, video, entertainment, news, sports), available in quality reception. The choices are just unlimited with INTERNET TV. Hold your remote control and everything is just a click away. This study is limited to the concept introduced. The respondent's understanding of the concept is reflected on the data which may affect the accuracy of the analysis. Data analysis is based on the research framework. This quantitative descriptive study explores the following market factors : purchase intentions (behavior); needs, likes, dislikes, important considerations, willingness to pay, superiority over substitute product, influences (attitude); perceived users and demographics (subjective norms). Attitude and subjective norms indicators were compared with behavior indicator. Research findings and discussion were presented in three parts, specifically to address the three research objectives. Product evaluation determines features that the market considers as Internet TV strengths and weaknesses. Value Analysis substantiates how much the market is willing to pay for Internet TV, among set packages and bundle. Segment analysis identifies the market segment most likely to use Internet Television.